Parents’ Promotion of Challenges scale in adolescent elite athletes - Julia Raimundi, María (2019)
Background: Parents’ promotion of challenges is a resource for adolescents’ positive development and, specifically, it can constitute a resource for adolescents who engage in a high- commitment activity such as elite sports. Objectives: The aim of this work is to present the psychometric properties of the Parents’ Promotion of Challenges Scale in elite athletes and to evaluate the contribution of this variable in the optimal experience, or flow, of these adolescents. Method: A total of 276 adolescents aged between 11 and 19 years (M = 15.71; SD = 1.49) representing Argentinean national teams of different sports participated in the study. Fifty four percent (54%) were males (n = 149) and 46% were females (n = 127). The participants answered a socio- demographic questionnaire, the Parents’ Promotion of Challenges Scale (EPDP), and the Flow State Scale for Adolescents. Results: The Confirmatory Factor Analysis, Component of Variance Analysis and Generalizability Analysis showed adequate indicators of validity and reliability for the EPDP (GFI = .99; AGFI = .98; CFI = 1; RMSEA = 0.0; RMR = .06; SRMR = .06; relative G = .82; absolute G = .81). Parents’ promotion of challenges contributes to the flow through the support dimension and it is only significant for women. Conclusions: This work provides an instrument for professionals working with adolescents and allows to contribute to promote positive experiences in elite sport.